Some aspects of elimination of grammatical ambiguity separate word forms in belles-lettres texts (based on prose and poetical compositions) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
This article examines qualitative and quantitative data obtained in the result of algorithm using for automatic elimination of grammatical ambiguity of separate word forms which appear in the text as proper and common names.
Keywords: grammatical ambiguity; disambiguation (elimination of ambiguity of separate word forms); algorithm; proper name; common name